EFFECT OF STARVATION ON THE BIOCHEMICAL COMPOSITION OF CLARIAS BATRACHUS(LINN.) - BANO, MISS YAGANA (Fishery Technology, 2017)
Marked changes were observed in different chemical constituents of Clarias batrachus during starvation. The nitrogen and protein fractions showed a definite pattern of variations. The highest values of these were recorded on lOth day of starvation and thereafter values declined gradually. On the other hand, the acid soluble phosphorus exhibited a reverse trend, increasing graduaUy from the first to the 30th day of starvation. These changes have been attributed mainly to the energy and metabolic demands of the starving fish.